Impact of the diverse cardiotonic steroids on beta-amyloid precursor protein level - Petrushanko, Irina Yu.; Lisitskii, Denis R.; Strelkova, Maria A.; Tolstova, Anna P.; Fedulov, Artemy P.; Filonov, Filipp A.; Mitkevich, Vladimir A.; Makarov, Alexander A. (Frontiers in Pharmacology, 2025)
Endogenous cardiotonic steroids (CTS), which are specific ligands of Na,K-ATPase, have been detected not only in blood plasma but also in cerebrospinal fluid and in the brain tissue. Consequently, the role of CTS in the central nervous system has gained increasing relevance. Na,K-ATPase serves not only as a receptor for CTS but also as a target for beta-amyloid (Aβ42). Previously, we demonstrated that ouabain binding to Na,K-ATPase prevents Aβ42-induced activation of Src kinase and the subsequent change in the level of the amyloid precursor protein (APP) in human neuroblastoma SH-SY5Y cells. In this study, we characterized the effects of other CTS—marinobufagenin, bufalin, and digoxin, on APP level in these cells. We found that, unlike ouabain, bufalin and digoxin increased APP levels in cells independently of Aβ42. Marinobufagenin amplified the increase of the general APP level caused by Aβ42. In contrast, the addition of Aβ42 in the presence of bufalin or digoxin does not further elevate APP levels. Src kinase activation is observed only with marinobufagenin. This suggests that unlike Aβ42, which activates Src kinase, the CTS-induced rise in APP occurred through a Src-independent pathway. CTS does not lead to the accumulation of APP in neurites. Furthermore, ouabain, marinobufagenin, and digoxin reduce the rise in APP that Aβ42 induces in neurites. Molecular modeling data indicate that CTS binding to Na,K-ATPase alters the number of contacts formed between the enzyme and subsequently bound Aβ42. It means that CTS binding to Na,K-ATPase alters its interaction with Aβ42. Taken together, these results show that endogenous CTS are important regulators that can maintain the balance between APP and beta-amyloid in the brain.